UPAYA PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN METODE INKUIRI DI KELAS IV SDN 060843 MEDAN TA 2013/2014 - Husna Tambunan (JURNAL TEMATIK, 2014)
Classroom action research aims to improve the activity and student learning outcomes with the application of inquiry learning methods. The study consisted of 2 cycles of the number of students 25. Collecting data using achievement test, student questionnaire responses, and observations of students in learning activities with the method of inquiry.Data analysis using quantitative techniques and qualitative techniques by linking existing data. The analysis showed: (1) an increase in the activity of the students are in the first cycle of acquisition activity by 61.25% students and 75.63% with enough categories. In the second cycle increased to 92.50% with very good category. (2) an increase in student learning outcomes in the first cycle is the average value of student learning outcomes for cognitive assessment was increased to 82 disiklus 60 to II with the percentage of students who obtained excellent learning predicate 96%. For the assessment of students psychomotor also increased in the first cycle is the highest score obtained by the students increased 3.30 to 3.40 in the second cycle with the percentage of students who received either 72% predicate learning. For the assessment of affective (honest, discipline and cooperation) also increased in the first cycle is 12% to 48%. Based on the above results it can be concluded that the application of the inquiry method can improve the activity and learning outcomes of students in the fourth grade SDN.060843 Medan